Effects of Hard Surface Grinding and Activation on Electroless-Nickel Plating on Cast Aluminium Alloy Substrates. (21st September 2014) - Ajibola, Olawale Olarewaju; Oloruntoba, Daniel T.; Adewuyi, Benjamin O.
Abstract : This work examined effects of hard surface polishing grits and activation on electroless-nickel (EN) plating on cast aluminium alloy substrates in sodium hypophosphite baths. As-received aluminium alloy sample sourced from automobile hydraulic brake master cylinder piston was melted in electric furnace and sand cast into rod. The cast samples were polished using different grits (60 μ m–1200 μ m) before plating. The effects on adhesion, appearance, and quantity of EN deposits on substrates were studied. Observation shows that the quantity of EN deposit is partly dependent on the alloy type and roughness of the surface of the substrates, whereas the adhesion and brightness are not solely controlled by the degree of surface polishing. The best yield in terms of adhesion and appearance was obtained from the activation in zincate and palladium chloride solutions. Higher plating rates (g/mm 2 /min) of3.01 E - 05, 2.41 E - 05, and2.90 E - 05 were obtained from chromate, zincate, and chloride than8.49 E - 06, 8.86 E - 06, and1.69 E - 05 as obtained from HCl etched, NaOH, and H2 O activated surfaces, respectively.